Reflections on Service-learning: Student Experiences in a Sport-based Youth Development Course. Issue 7 (2nd September 2017) - Whitley, Meredith A.; Farrell, Kelly; Maisonet, Cindy; Hoffer, Andrew
Abstract : Service-learning courses provide students with practical opportunities to enhance their learning and development in the field, along with getting students engaged in different communities and settings. However, there are still many challenges to designing and offering effective service-learning courses, such as requiring all students to participate in the service-learning component and creating a larger workload for teachers. The purpose of this article is to provide a detailed description of a service-learning course in the sport-based youth development field that addresses these concerns. By partnering with a community-based organization, students enrolled in this service-learning course were able to participate in two ways: (1) serving as a student leader in the 10-week program or (2) serving as a formative evaluator by watching the videotaped sessions each week and providing constructive feedback to their peers. Through an independent study option, some students could also serve as summative evaluators of the program. This article describes the service-learning course and sport-based youth development program, with in-depth reflections from three graduate students detailing their experiences serving in different roles. The article also provides practical implications for teachers and practitioners, serving as one example of a successful service-learning course that maximizes student engagement, learning and development.